Review: Geological Structure impacts to hydrocarbon potential and active faults in the East Java Basin, Indonesia - Fahrudin; Yoga Aribowo (UIR PRESS, 2024)
Review of the geological structure patterns in the East Java Basin (EJB) to understand the geodynamics has implicated to the hydrocarbon potential and active faults. However, the impact of those structures on hydrocarbon potential and active faults is unclear. This study reviewed structure patterns using surface and subsurface data, GPS, seismicity and tremors in the East Java Basin, Indonesia and Nankai Trough, Japan. In EJB, Indonesia, the tectonic setting is constrained by the Rembang Fault. The north of the Rembang Fault, the pattern exhibits NE-SW structures, while to the south, it shows W-E structures. The results indicate that the upper crust (including ophiolitic basement) has greater density to the north than to the south. Thus, vertical motion of the crust is more dominant than lateral motion to the north of the Rembang Fault. This vertical motion may trigger the reactivation of the Meratus Fault (weak zone or as active fault) located on the northern platform (e.g., the Bawean earthquake on March 22, 2023). Conversely, to the south of the Rembang Fault, there is a significant hydrocarbon potential associated with W-E structures. Those structures could form by subduction and collision tectonic. Similary, tectonic backstop may account for presence of structures in Nankai Trough, Japan.